THE ROLE OF TECHNOLOGY IN ONLINE LEARNING: AN EXAMINTATION TOWARDS ENGLISH TEACHERS’ PERCEPTION AND PRATICES - Naajihah Mafruudloh; Fais Wahidatul Arifatin; Uswatun Chasanah (IKIP Siliwangi, 2021)
Information technology is well developed today. This is shown by several applications that support online activities, social activities, commerce, services, and learning. In this pandemic situation (covid-19), several institutions provided policies to carry out online learning to prevent and minimize the spread of the Covid-19 virus. In this case, the institution committees ask the teachers and lecturers to provide online learning to students, especially in learning English. The purpose of this study was to determine the teachers' perceptions in online language learning. Researchers used a questionnaire instrument to conduct surveys and interviews to obtain qualitative data. This is aimed to observe the teachers’ perception towards online language teaching practices and changes in teaching to online teaching. The things encountered during learning, as well as obstacles faced by the English teacher. In online learning, teachers must be able to involve students so that the situation runs like face-to-face learning. The final results of this study will be useful for online language teachers, institutions, and all aspects involved in education.